Urban sustainability and river restoration. Green and blue infrastructure. - Perini, Katia; Sabbion, Paola (Wiley Blackwell, 2017)
This book considers the integration of green and blue infrastructure in cities as a strategy useful for acting on causes and effects of environmental and ecological issues. River restoration projects are unique opportunities for sustainable development and smart growth of communities, providing multiple environmental, economic, and social benefits.This book analyzes initiatives and actions carried out and developed to improve environmental conditions in cities and better understand the environmental impact of (and in) dense urban areas in the United States and in Europe.
Keywords: Städtebau; Stadtentwicklung; Stadtregion; Wasser; Fluss; Ufer; Stadtbegrünung; Grünfläche; Vegetation; Ökosystem; Stadtökologie; Umweltschutz; Verdichtungsraum; Beispielsammlung; Stadtumbau; Nachhaltigkeit; Uferbebauung; Ufergestaltung; Stadtgrün; Klimaschutz